2019
DOI: 10.1111/tbed.13222
|View full text |Cite
|
Sign up to set email alerts
|

Population structure and antimicrobial resistance traits of avian‐origin mcr‐1 ‐positive Escherichia coli in Eastern China, 2015 to 2017

Abstract: Recent emergence of mcr-1-positive Escherichia coli (MCRPEC) is causing serious concern around the world. Due to poultry-origin E. coli holding zoonotic potential, the improved understandings of MCRPEC population structure and antimicrobial resistance are critical to public health purposes. This study provided novel insights into the molecular epidemiology of avian-origin MCRPEC. For the mcr genes prevalence study, we analysed 1,360 E. coli recovered from avian colibacillosis in eastern China from 2015 to 2017… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
26
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 35 publications
6
26
2
1
Order By: Relevance
“…In this study, all the Salmonella resistance to PB, however, only 6.0 of the isolates carried mcr−1 which was different from the report that there was a close positive correlation between the resistance phenotypes and genotypes of the isolates [39].…”
Section: Discussioncontrasting
confidence: 99%
“…In this study, all the Salmonella resistance to PB, however, only 6.0 of the isolates carried mcr−1 which was different from the report that there was a close positive correlation between the resistance phenotypes and genotypes of the isolates [39].…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, the mcr-1 positive isolates showed higher resistance to PB than the mcr-1 negative E. coli isolates in this study, which suggested that there was a close positive correlation between the resistance phenotypes and genotypes of the mcr-1 positive isolates. This result is consistent with other reports (Huang et al, 2017;Shen et al, 2018;Zhuge et al, 2019).…”
Section: Discussionsupporting
confidence: 94%
“…In the current study, we noticed a high rate of resistance to AMP, AMO, and FLO in the mcr-1 positive isolates similar to a report in Eastern China from 2015 to 2017 (Zhuge et al, 2019), suggesting that these drugs may have been widely used in poultry farming. Most of the mcr-1 positive isolates showed susceptibility to AC, which was associated with the infrequent use of this drug, and the result was consistent with other reports (Dominguez et al, 2018).…”
Section: Discussionsupporting
confidence: 89%
“…However, levels of colistin resistance are consistently low. The gene mcr-1 has also been identified in bacteria from sheep (Tang et al, 2019), poultry (ducks, geese, and pigeons) (Zhang et al, 2018;Zhuge et al, 2019), companion animals (dogs and cats) (Sun et al, 2016;Zhang et al, 2016;Lei et al, 2017;Wang et al, 2018a;Ortega-Paredes et al, 2019;Rumi et al, 2019), and even wild animals (Liakopoulos et al, 2016;Mohsin et al, 2016;Ruzauskas and Vaskeviciute, 2016;Unger et al, 2017;Bachiri et al, 2018;Oteo et al, 2018) (Table 1 and Supporting Information Table S1). The first report of a wild animal carrying mcr-1 gene could be traced back to 2012, when Liakopoulos et al identified five mcr-1-positive E. coli from Larus dominicanus (n = 50) in Argentina, and all mcr-1 genes were located on IncI2 plasmids (Liakopoulos et al, 2016).…”
Section: Prevalence Of Mcr Genes In Animals and Animalderived Food Prmentioning
confidence: 99%